Isotype-switched follicular lymphoma displays dissociation between activation-induced cytidine deaminase expression and somatic hypermutation. Issue 1 (2nd January 2016) - Scherer, Florian; Navarrete, Marcelo A.; Bertinetti-Lapatki, Cristina; Boehm, Joachim; Schmitt-Graeff, Annette; Veelken, Hendrik
Abstract : In B-cells, activation-induced cytidine deaminase (AID) is required for somatic hypermutation (SHM) and class switch recombination (CSR) of immunoglobulin genes. AID introduces mutations in immunoglobulin variable regions (IGV) during B-cell receptor affinity maturation, but may also introduce aberrant mutations into non-immunoglobulin genes, most commonly BCL6. Follicular lymphoma (FL) B-cells constitutively express AID and undergo CSR, SHM and aberrant SHM. We have studied AID expression, the presence of SHM mutations, CSR, and aberrant SHM in BCL6 in a cohort of 75 FL patients. Whereas IgM-expressing (non-switched) FL were characterized by an expected positive correlation between AID and IGV and BCL6 mutations, isotype-switched FL showed dissociation between AID expression and aberrant SHM, and inverse correlation between SHM and AID expression. Our results unveil two manifest biological subgroups of FL and indicate that the specific dissociation between AID and SHM after isotype switch may correlate with the clinical outcome of this heterogeneous disease.